Respuestas

2013-10-30T19:50:45+01:00
2/3 + x/4 = 3/4 - x/3  

x/4 + x/3 = 3/4 - 2/3

reducimos a comun denominador   m.c.m = 12

(3x + 4x) / 12   = (9- 8 ) / 12

3x + 4x = 9-8

7x = 1

x = 1/7

============================================


2/3² = 2x - 8/7 + 2³  

2/9 = 2x –8/7 + 8  

2x = 2/9 +8/7 –8  

2x = 14 + 72 – 504  / 63
 

126 x = -418  

x = -418 / 126 = -209 / 63

==========================================

5/4 . 3 + x/4 = 2/3 - 2/3x  

15 / 4 + x/4 = 2/3 –2/3 x  

x/4 + 2x/3 = 2/3 – 15/4  

5/3 x = -37/12  

60x = -111  

x = -111/60